Dharamjali speleothem trace elements and stable isotopes - Alena Giesche; David A Hodell; Cameron A Petrie; Gerald H Haug; Jess F Adkins; Birgit Plessen; Norbert Marwan; Harold J Bradbury; Adam Hartland; Amanda D French; Sebastian F M Breitenbach (PANGAEA, 2023)
A 25-cm long predominantly aragonite stalagmite was collected November 2, 2005 from Dharamjali Cave (29.5°N, 80.2°E) in the central Himalayas. This dataset contains stable isotope, trace element, XRF, U/Th dating, and dripwater data. The age model spans 4.2 to 2.3 ka BP, and the dataset records seasonal shifts in hydroclimate from 4.2 to 3.1 ka BP. Using the DHAR-1A half of the speleothem, 750 samples were milled at 100–300 μm resolution for stable isotope analysis (δ18O and δ13C) and analyzed at GFZ Potsdam. Further high-resolution stable isotope analysis at the University of Cambridge included 876 samples from the bottom 4 cm of the mirroring slab DHAR-1B, covering c. 4.2–3.6 ka BP. The δ44/40Ca measurements were made on 60 aragonite samples of aragonite and 1 calcite sample milled between 4.2 and 2.8 ka BP. The elemental composition of DHAR-1B was determined first with an Avaatech XRF scanner at the University of Cambridge, and later using laser ablation inductively-coupled plasma mass spectrometry (LA-ICP-MS) at the University of Waikato. U-series dating was performed at Caltech on 22 samples. Twelve U-series ages (between 2.55 and 4.14 ka BP) were used to construct the age models, using ensembles of 2000 Monte Carlo simulations for each proxy using the MATLAB-based COPRA script (Breitenbach et al., 2012, https://doi.org/10.5194/cp-8-1765-2012).